2021
DOI: 10.1111/ans.16736
|View full text |Cite
|
Sign up to set email alerts
|

Complication profile of augmentation cystoplasty in contemporary paediatric urology: a 20‐year review

Abstract: Background The aim of this study was to describe the complication profile of augmentation cystoplasty in contemporary paediatric urology as well as its effect on bladder metrics. Methods Consecutive operative cases were retrospectively reviewed at a single institution over 20 years (1999–2019). Short‐ and long‐term outcomes and complications following augmentation cystoplasty were defined. Results Of the 71 operative cases; the most common underlying diagnoses were neurogenic bladder (34%), exstrophy‐epispadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…The improved VUD parameters, including the MBC, MDP, and bladder compliance, are consistent with previously published data for AC ( 16 18 ). The results also demonstrated stable levels of serum creatine during follow-up, indicating preserved renal function.…”
Section: Discussionsupporting
confidence: 91%
“…The improved VUD parameters, including the MBC, MDP, and bladder compliance, are consistent with previously published data for AC ( 16 18 ). The results also demonstrated stable levels of serum creatine during follow-up, indicating preserved renal function.…”
Section: Discussionsupporting
confidence: 91%
“…Augmentation cystoplasty is a surgical intervention that can significantly and continuously improve the quality of life in children. However, careful patient selection and appropriate preoperative counseling are essential, given the potential complications of urinary leakage and urinary tract stone disease and the fact that augmentation cystoplasty is an independent risk factor for bladder malignancy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…88 Congregated evidence generated by the NICE and SBA guidelines, as well as recent reports, has shown that augmentation cystoplasty improves bladder capacity and reduced detrusor pressure, decreasing the likelihood of incontinence, specifically in older pediatric patients with NLUTD. 29,40,90,91 Augmentation cystoplasty increases the need for intermittent catheterization; however, it may also improve patient satisfaction and quality of life. 40,91,92 In patients where both augmentation cystoplasty and BTX-A therapy are viable options, analysis shows that augmentation cystoplasty is costeffective for patients likely to benefit from incontinence treatment for more than 10 years.…”
Section: █ Recommendation 12: Vesicostomy (Weak Recommendation Le Iii...mentioning
confidence: 99%